DAPROG: dojo de aprendizagem de programação de computadores - Oliveira, Paulo Cezar de (2019)
Software developers have organized face-to-face meetings to discuss, program and share knowledge. In many of these meetings, the purposes range from fun, facing challenges, and professional software development. Among these meetings, Coding Dojos are distinguished by the interest of its participants in learning new software development practices and learning new programming languages. However, Coding Dojos, in any of its styles, when employed for teaching in the classroom may not be as motivating and effective for student learning. In this work, we present the CPLD (Computer Programming Learning Dojo), a proposal that intends to adapt Coding Dojos to the academic environment and evaluate if the participation of the students in CPLD presents effective and motivating results for learning of new programming languages. This work was carried out in two stages. In the first one, we participated in Coding Dojo meetings held in a teaching institution, a free software event and in a technology company with the intention of getting involved in the activities. At each meeting, we applied questionnaires to find out if Coding Dojo allows any learning. We found that 78.5% participants learned something and 81% of them could better understand the programming language used in that Coding Dojo. In another moment, we presented to the 53 undergraduate students in the areas of Information Systems and Computer Engineering the Computer Programming Learning Dojo. And the results were: 72.2% stated that they liked the proposed activity and 74.1% of them liked its that teaching methodology. And the same percentage of 74.1% of the respondents stated that their level of knowledge in a given language presented good improvement. The results presented in this study show that there was a good acceptance of the activity proposed to the students of those case studies. Therefore, we can observe that by involving students in both the learning process and the process of imparting their knowledge, the classes can become increasingly attractive and reach a more considerable number of students in the classroom.